2001
DOI: 10.1309/b0dd-4m7h-gjg1-7kcw
|View full text |Cite
|
Sign up to set email alerts
|

E-Cadherin Reactivity of 95 Noninvasive Ductal and Lobular Lesions of the Breast

Abstract: Studies suggest that E-cadherin is useful to classify epithelial breast lesions as ductal or lobular, but extensive experience with this antibody is lacking. We studied reactivity of lesions with classic and indeterminate morphologic features. We reviewed 95 lesions and divided them into unanimous and nonunanimous diagnosis groups; the unanimous group served as benchmark lesions to which E-cadherin reactivity could be standardized and compared. All 37 ductal lesions in the unanimous group had strong, diffuse E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 34 publications
4
32
0
1
Order By: Relevance
“…In cases with non-specific morphologic characteristics, categorization can be performed through IHC, and E-cadherin is currently used to differentiate between the two. The majority of ductal carcinomas express cytoplasmic E-cadherin, whereas most lobular carcinomas lack expression of E-cadherin [3,15,16] . In addition, the differences in CKs expression may be used: highmolecular-weight CK (clone 34βE12) is usually expressed by lobular carcinomas, but is absent or expressed at low levels in most cases of DCIS [3,17,18] .…”
Section: Lobular or Ductal Carcinoma: E-cadherin Ck8mentioning
confidence: 99%
“…In cases with non-specific morphologic characteristics, categorization can be performed through IHC, and E-cadherin is currently used to differentiate between the two. The majority of ductal carcinomas express cytoplasmic E-cadherin, whereas most lobular carcinomas lack expression of E-cadherin [3,15,16] . In addition, the differences in CKs expression may be used: highmolecular-weight CK (clone 34βE12) is usually expressed by lobular carcinomas, but is absent or expressed at low levels in most cases of DCIS [3,17,18] .…”
Section: Lobular or Ductal Carcinoma: E-cadherin Ck8mentioning
confidence: 99%
“…48 In addition, although E-cadherin is very useful as an adjunct in differentiating ductal from lobular lesions, morphologically unequivocal cases of LCIS and invasive lobular carcinoma have been shown to demonstrate focal E-cadherin positivity. 49,50 Dabbs et al 51,52 recently reported the utility of p120-catenin in both classic and pleomorphic variants of LCIS. Characteristically, this antibody is diffusely localized to the cytoplasm in cases of lobular neoplasia, whereas in ductal lesions it remains localized to the membrane.…”
Section: Immunophenotypementioning
confidence: 99%
“…Reduced expression of E-cadherin has been reported in invasive ductal carcinoma whereas lobular carcinoma in situ and invasive lobular carcinoma show complete loss of the protein. [6][7][8][9][10][11][12][13][14][15][16] A report on invasive lobular carcinomas with adjacent lobular carcinoma in situ demonstrated not only loss of Ecadherin expression but also the simultaneous loss of beta-, gamma-and alpha-catenin protein expression. 15 More recently, Sarrio et al 17 demonstrated that the loss of E-cadherin along with the cytoplasmic localization of p120-catenin characterizes lobular breast cancers and suggested that p120-catenin plays a role in mediating the oncogenic effects of Ecadherin loss in these cancers.…”
mentioning
confidence: 99%